Schur's Q-functions, spin characters and the Kronecker products of the spin irreducible. Representations of symmetric groups - Salam, M. Abdus (Utilitas Mathematica, 1997)
A new simple algorithm for the calculation of the spin characters of the symmetric groups has been developed using the properties of symmetric functions. This leads to a more efficient method of calculating the Kronecker product of spin irreducible representations of symmetric groups. A computer program called CHAR computes the individual characters and character tables using this method and using these characters computes the Kronecker products of the spin irreducible representations.